Physiological and transcriptomic analyses reveal the regulatory mechanisms for the adaptation of Quercus robur to shade conditions - Xiong Huang; Qiuhong Hu; Mengke Dou; Cai Liu; Jiangtao Fan; Jia Liu; Peng Zhu (BMC Plant Biology)
Abstract Background As an important multipurpose tree species, the growth and development of Quercus robur are significantly influenced by shading conditions. Although the critical role of shading in plant growth and development has been well established, the responses of oak trees to shading remain poorly understood. This study aimed to investigate the physiological and transcriptomic changes in Q. robur under varying shade conditions. Results Shade had a significant impact on the growth and physiological indicators of Q. robur. As the shading level increased, the plant height, ground diameter, Pn, PRO content, and SOD activity of Q. robur initially increased before subsequently decreasing. In contrast, CHL-a, CHL-b, Car content, SP content, and POD activity exhibited an increasing trend. Transcriptome sequencing was performed on Q. robur samples subjected to different shade treatments: no shade (T1), 40% shade (T3), and 80% shade (T5). Following rigorous quality control, we obtained 57.62 Gb of high-quality sequencing data, and 3,795 DEGs (T1-VS-T3 group), 7,852 DEGs (T1-VS-T5 group), and 7,139 DEGs (T3-VS-T5 group) were identified. KEGG pathway analyses of 978 overlapping DEGs identified crucial involvement of photosynthesis-antenna proteins and plant hormone signal transduction pathways. RT-qPCR validation of six DEGs confirmed the reliability of the transcriptome sequencing data. Notably, we demonstrated significant associations (p < 0.05) between 516 core genes and key growth-physiological traits by correlation analysis. Conclusions This study provides insights into the patterns of growth changes and physiological responses in Q. robur under shading conditions. Q. robur has adapted to shade conditions by inhibiting photosynthesis, synthesizing chlorophyll and Car, activating the antioxidant system, and regulating osmoregulatory substances. Furthermore, this study elucidated the transcriptional responses of Q. robur to shading, thereby revealing the molecular mechanisms underlying shade adaptation. This research provides a foundational understanding of physiological and molecular mechanisms of Q. robur in shade conditions.